2016
DOI: 10.1021/acs.orglett.6b00755
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Generation of Benzyl Cations That Selectively Cross-Link Guanine and Cytosine in DNA

Abstract: UV irradiation of several aryl boronates efficiently produced bifunctional benzyl cations that selectively form guanine-cytosine cross-links in DNA. Photoinduced homolysis of the C–Br bond took place with the aryl boronate bromides 3a and 4a, generating free radicals that were oxidized to benzyl cations via electron transfer. However, photoirradiation of the quaternary ammonium salts 3b and 4b led to heterolysis of C–N bond, directly producing benzyl cations. The electron-donating group in the aromatic ring gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 45 publications
(72 reference statements)
2
40
0
Order By: Relevance
“…Then Li and Greenberg demonstrated that photoirradiation of the modified thymidines generated both 5‐(2′‐dexoyuridinyl)methyl radical and cation, whereas only cation intermediates directly produced DNA ICL products. Recently, Peng and co‐workers found that several bifunctional aromatic boronates cross‐linked DNA through carbocation formation upon 350 nm irradiation …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then Li and Greenberg demonstrated that photoirradiation of the modified thymidines generated both 5‐(2′‐dexoyuridinyl)methyl radical and cation, whereas only cation intermediates directly produced DNA ICL products. Recently, Peng and co‐workers found that several bifunctional aromatic boronates cross‐linked DNA through carbocation formation upon 350 nm irradiation …”
Section: Introductionmentioning
confidence: 99%
“…There are still only a few compounds with limited structure variations that have been reported to induce DNA cross‐linking through the carbocation pathway upon photoirradiation. All of the existing bifunctional compounds capable of efficiently cross‐linking DNA via photogenerated carbocations contain boronate ester groups (e.g., 1 a’ and 1 b’ ) . However, in species such as 1 a’ and 1 b’ the carbocations are generated by dissociation of the leaving groups L, and the role of the boronate ester functionality appears to be as a modulator of the cationic intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous work,[41] compounds 2a–5a with Br as a leaving group were synthesized via borylation of the corresponding 1-bromobenzene 6, 10, 13 , or 16 using n-butyllithium and isopropoxyboronic acid pinacol ester followed by bromination with N -bromosuccinimide (NBS) and azobisisobutyronitrile (AIBN) (Note: To be consistent, the numbering shown for 1a and 1b is used for all compounds described in this paper). Compound 6 is commercially available, while 10, 13 , and 16 were synthesized starting from methoxy substituted benzenes 8, 12 , and 15 .…”
Section: Resultsmentioning
confidence: 99%
“…or modified bases with possibilities for cross-linking(Stephenson et al 2011;Wang et al 2016; Zhang and Paukstelis 2016) etc.). On a recent paper, Tomàs Gamasa et al(Tomas- Gamasa et al 2015) have reported formation of selective, reversible and highly thermostable DNA interstrand cross-links based on the reversible imine chemistry concept.…”
mentioning
confidence: 99%